Antimicrobial activity of the essential oil of ginger (Zingiber officinale Rasc.) on seven test organisms. - Pelobello, Ma. Lourdes Frio (1994.)
This study was undertaken to determine the antimicrobial activity of the essential oil of ginger (Zingiber officinale Rosc.) on seven test organisms. The results indicated that four of the seven organisms were found to be highly susceptible to ginger oil, namely: Bacillus subtilis, Escherichia coli, Candida albicans and Staphycoccus aureus. On the other hand, three test organisms were found to be resistant to the ginger oil. These are the Pseudomonas aeroginosa , Mycobacterium avium and Saccharomyces cerevisiae.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Ginger